2011
DOI: 10.1073/pnas.1109101108
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular phosphatidylserine is essential for retrograde membrane traffic through endosomes

Abstract: Phosphatidylserine (PS) is a relatively minor constituent of biological membranes. Despite its low abundance, PS in the plasma membrane (PM) plays key roles in various phenomena such as the coagulation cascade, clearance of apoptotic cells, and recruitment of signaling molecules. PS also localizes in endocytic organelles, but how this relates to its cellular functions remains unknown. Here we report that PS is essential for retrograde membrane traffic at recycling endosomes (REs). PS was most concentrated in R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
179
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 168 publications
(194 citation statements)
references
References 30 publications
13
179
2
Order By: Relevance
“…CvpB Modulates the Intracellular Levels of PI(3)P. Host PIs and their metabolism are known targets of a number of bacterial pathogens; we thus investigated whether Coxiella uses CvpB to manipulate pathways controlled by PS and/or PI(3)P. Besides its role as a signaling lipid during apoptosis, it has been reported that PS plays an important role in retrograde traffic from the plasma membrane to the Golgi complex (22). We therefore transfected U2OS cells with mCherry or CvpB-mCherry and monitored retrograde transport by incubating cells with 1 μg/mL FITC-labeled Cholera toxin B subunit (CtxB).…”
Section: Cvpb Localizes At Ccvs and Early Endosomes Triggering Endosomementioning
confidence: 99%
“…CvpB Modulates the Intracellular Levels of PI(3)P. Host PIs and their metabolism are known targets of a number of bacterial pathogens; we thus investigated whether Coxiella uses CvpB to manipulate pathways controlled by PS and/or PI(3)P. Besides its role as a signaling lipid during apoptosis, it has been reported that PS plays an important role in retrograde traffic from the plasma membrane to the Golgi complex (22). We therefore transfected U2OS cells with mCherry or CvpB-mCherry and monitored retrograde transport by incubating cells with 1 μg/mL FITC-labeled Cholera toxin B subunit (CtxB).…”
Section: Cvpb Localizes At Ccvs and Early Endosomes Triggering Endosomementioning
confidence: 99%
“…To confirm that the cluster is indeed derived from the ERC, we exploited a recent observation that phosphatidylserine (PS) is enriched in membranes of the ERC (Uchida et al, 2011); PS was detected using a PS-specific probe, the C2 domain of lactadherin (LactC2). As shown in Fig.…”
Section: Accumulation Around Centrosomes Of Proteins Trafficking Thromentioning
confidence: 99%
“…An expression vector for FLAG-tagged dynamitin (Hirose et al, 2004) was provided by Mitsuo Tagaya (Tokyo University of Pharmacy). A LactC2 cDNA fragment (Uchida et al, 2011) (provided by Hiroyuki Arai, University of Tokyo) was initially subcloned into pcDNA3-mRFP (provided by Roger Tsien). The mRFP-LactC2 cDNA fragment was then amplified by polymerase chain reaction from pcDNA3-mRFP-LactC2 and cloned into the pGEX-6P-1 vector (GE Healthcare).…”
Section: Plasmidsmentioning
confidence: 99%
“…Two recycling-endosome-localized proteins, evectin-2 (also known as PLEKHB2) and SMAP2, have recently been shown to be essential for the retrograde transport of CTxB at the recycling-endosome-toGolgi step (Matsudaira et al, 2013;Uchida et al, 2011). Evectin-2 contains a pleckstrin homology (PH) domain which specifically binds phosphatidylserine (PtdSer) and this interaction is required for its function and localization to PtdSer-enriched recycling endosomes.…”
Section: Introductionmentioning
confidence: 99%
“…Recycling endosomes are emerging as an essential sorting station for some retrograde cargo proteins, such as MPR300 (Lin et al, 2004;McKenzie et al, 2012), the Shiga toxin B-subunit (STxB) (McKenzie et al, 2009(McKenzie et al, , 2012, and the cholera toxin B-subunit (CTxB) (Uchida et al, 2011); these proteins traffic sequentially from the plasma membrane to early endosomes, then to recycling endosomes and finally to the Golgi (Taguchi, 2013). Two recycling-endosome-localized proteins, evectin-2 (also known as PLEKHB2) and SMAP2, have recently been shown to be essential for the retrograde transport of CTxB at the recycling-endosome-toGolgi step (Matsudaira et al, 2013;Uchida et al, 2011).…”
Section: Introductionmentioning
confidence: 99%